PERANAN POLA ASUH ORANG TUA TERHADAP KUALITAS HIDUP REMAJA PERKOTAAN - Pamela Hendra Heng; Naomi Soetikno; Amala Fahditia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
In an effort to improve the progress of the Indonesian nation, it is necessary to pay attention to all levels of society, especially the young people who will be the pillars of the Indonesian nation in the future. One fourth of Indonesia's population is children and adolescents. Other studies have shown that parenting can influence a child's level of self-confidence, academic performance, and children's behavior. This research was to examine the